Medication Adherence Factors Among the Elderly With Hypertension in Nursing Homes in Indonesia (International Journal of Studies in Nursing, 2021)
Background: Hypertension is a common chronic disease among the Indonesian elderly. One of the biggest communities of the elderly in Indonesia was in Nursing homes, which were organized by the government or private sector. Keeping medication adherence for hypertension is the tough challenge for elderly in Nursing homes since the number of complication increase every year such as Stroke, heart disease, and kidney renal failure. Purpose: This study is to identify the predictor among related factors with medication adherence of the elderly with hypertension in nursing homes Method: The quantitative study recruited 152 respondents with a mean age of 63 to 64 years old. Translated Hill bone instrument was used to explore the medication adherence and demographic related factors such as age, marital status, education level, gender, type of medication, economic source, family type, and religion. Result: The study revealed the significant association between economic source, age, medication, and education level as the factors predicting medication adherence. Conclusion: The study suggested that health providers should be more considerate in assisting the no formal education elderly or lower education level elderly and also their attitude on medication. Collaborative care approach should facilitate the education of the elderly about hypertension, the benefits of medications, the importance of continuous medication use especially in the treatment and management of hypertension.